Circular RNA hsa_circ_0001666 and Its Target Protein ETV4 AS Potential Biomarkers for Crohn's Disease - Roushdy, Walaa N.; Ketat, Amel F.; Barghash, Nadia A.; Ibrahim, Abeer M.; Alfarjani, Fatma D. (Journal of Coloproctology, 2025)
Circular RNAs are stable non-coding RNAs that regulate key biological processes. Hsa_circ_0001666 was shown to be involved in several cancers and in chronic inflammatory diseases. It is overexpressed in Crohn's Disease (CD) and is associated with cell migration, invasion, epithelial-mesenchymal transition (EMT), and fibrosis. Hsa_circ_0001666 acts as a sponge for multiple microRNAs (miRNAs). Some of these miRNAs regulate the expression of ETS variant transcription factor 4 (ETV4), a protein regulating critical genes implicated in inflammation, invasion, and EMT.To assess the plasma relative expression levels of hsa_circ_0001666 and the ETV4 protein levels to evaluate their contribution to CD development and the possibility of utilizing them as potential non-invasive biomarkers for diagnosis of CD and assessment of the disease activity.The present study included 25 patients with active CD, 25 patients with inactive CD, and 25 healthy subjects as controls. The analysis of the relative expression of hsa_circ_0001666 in plasma was performed using the real-time quantitative polymerase chain reaction (qPCR) method. The ETV4 concentration in plasma was measured using an enzyme-linked immunosorbent assay (ELISA).Plasma expression levels of hsa_circ_0001666 and ETV4 protein were significantly higher in active and inactive CD patients than the healthy controls, and in active CD patients than in patients with inactive disease. Furthermore, there was a significant positive correlation between hsa_circ_0001666 to ETV4 expression in the three studied groups.Higher levels of hsa_circ_0001666 and ETV4 in CD patients suggest their role in disease development and activity, and their potential use as diagnostic biomarkers and therapeutic targets for CD management.
Keywords: Hsa_circ_0001666; ETV4; Crohn's disease; epithelial-mesenchymal transition; fibrosis